Secondhand smoke in cars: assessing children's potential exposure during typical journey conditions. Issue 6 (4th January 2012) - Semple, Sean; Apsley, Andrew; Galea, Karen S; MacCalman, Laura; Friel, Brenda; Snelgrove, Vicki
Abstract : Objective: To measure levels of fine particulate matter in the rear passenger area of cars where smoking does and does not take place during typical real-life car journeys. Methods: Fine particulate matter (PM2.5 ) was used as a marker of secondhand smoke and was measured and logged every minute of each car journey undertaken by smoking and non-smoking study participants. The monitoring instrument was located at breathing zone height in the rear seating area of each car. Participants were asked to carry out their normal driving and smoking behaviours over a 3-day period. Results: 17 subjects (14 smokers) completed a total of 104 journeys (63 smoking journeys). Journeys averaged 27 min (range 5–70 min). PM2.5 levels averaged 85 and 7.4 μg/m 3 during smoking and non-smoking car journeys, respectively. During smoking journeys, peak PM2.5 concentrations averaged 385 μg/m 3, with one journey measuring over 880 μg/m 3 . PM2.5 concentrations were strongly linked to rate of smoking (cigarettes per minute). Use of forced ventilation and opening of car windows were very common during smoking journeys, but PM2.5 concentrations were still found to exceed WHO indoor air quality guidance (25 μg/m 3 ) at some point in the measurement period during all smoking journeys. Conclusions: PM2.5 concentrations in cars where smoking takes place are high and greatly exceed international indoor air quality guidance values. Children exposed to these levels of fine particulate are likely to suffer ill-health effects. There are increasing numbers of countries legislating against smoking in cars and such measures may be appropriate to prevent the exposure of children to these high levels of secondhand smoke.